TCRβ repertoire of memory T cell reveals potential role for Escherichia coli in the pathogenesis of primary biliary cholangitis. (24th February 2019) - Hou, Xianliang; Yang, Yida; Chen, Jianing; Jia, Hongyu; Zeng, Ping; Lv, Longxian; Lu, Yingfeng; Liu, Xiangdong; Diao, Hongyan
Abstract: Background: Primary biliary cholangitis (PBC) is an organ‐specific, T cell‐mediated autoimmune disease which is characterized by the breakdown of self‐tolerance to the highly conserved pyruvate dehydrogenase complex, especially the pyruvate dehydrogenase E2 complex (PDC‐E2). However, the molecular mechanism of breakdown of self‐tolerance is still unclear. Methods: A combination of multiplex‐PCR and immune repertoire sequencing (IR‐seq) was used for a standardized analysis of memory T cell receptor (TCR) β‐chain repertoire of PBC patient and healthy volunteers. In vitro induction and expansion of human PDC‐E2163‐176 (human PDC‐E2)‐specific T cells and E coli PDC‐E231‐44/134‐147/235‐248 ( E coli PDC‐E2)‐specific T cells, and identified the human (and E coli ) PDC‐E2‐specific TCRβ repertoire by IR‐seq. Results: Primary biliary cholangitis patients have shorter complementarity‐determining region 3s (CDR3s), and higher degree of sequence overlap in the TCRβ repertoire of memory T cell. Moreover, altered insertion patterns and skewed TRBV segment usage were observed in PBC patients. With regard to the pathogenesis, the concentration of E coli was higher in PBC patients' faecal. The frequency of E coli (and human)‐specific TCRs was higher in the memory TCRβ repertoire of PBC patients compared with healthy controls. Importantly, the TCRβ repertoire characteristics were almost identical between E coli PDC‐E2‐related TCRs and human PDC‐E2‐related TCRs, including the patterns of TRBV usage, CDR3 length and amino acid composition. Conclusion: Our findings comprehensively revealed the TCRβ repertoire characterization of PBC patients, and provided a TCR molecular basis to understand the mechanism of cross‐recognition between human PDC‐E2 and E coli PDC‐E2, and the imbalance of immune tolerance in PBC.